Evaluation model for topology partition base on simulation run time - Wen-tang GE; Zhao-xin ZHANG; Bin LI (Tongxin xuebao)
Firstly,by analyzing the PDES mechanism,a variety of factors affecting simulation performance were summa-rized and classified,and the factor set influenced by topology partition result was found out; and then,by analyzing simulation run time,an evaluation model for topology partition was presented.The DDoS attack experiment results and model calculations are basically consistent in PDNS environment,and this proves the accuracy of the model.At last,by evaluating METIS algorithm and subnet elimination algorithm,the former algorithm has higher evaluation than the latter,by about 14%.The experimental results accord with the expectations,and prove the effectiveness of the model.